Patterns of maternal behaviour of ewes and sucking behaviour of lambs - GOUGOULIS (Δ.Α. ΓΚΟΥΓΚΟΥΛΗΣ), D. A.; KYRIAZAKIS (Η. ΚΥΡΙΑΖΑΚΗΣ), Ι.; FTHENAKIS (Γ. Χ. ΦΘΕΝΑΚΗΣ), G. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
In the present article the literature of maternal and sucking behaviour of sheep is reviewed. The article is divided into five sections: (i) Preparation of the ewe - lambing, (ii) Initiation of maternal behaviour - recognition of newborn lambs, (iii) Recognition between ewe and newborn lambs (auditory stimuli and ewe-lamb recognition, visual ewe-lamb recognition, olfactory cues for maternal behaviour, haptic cues in teat seeking by newborn lambs), (iv) Other patterns of ewe - lamb behaviour (other behavioural patterns immediately post-partum, behavioural patterns during lactation) and (v) Neuro-hormonal control of maternal behaviour. In general, studies of maternal and neonatal behavior of sheep contribute to development of management practices, resulting to decreased neonatal mortality, increase of meat production and improvement of animal health and welfare. They also confirm the importance of animal ethology as a veterinary speciality.